Deskripsi Kualitas Asap Cair Hasil Pirolisis Tempurung Kelapa dengan Metode Aliran Udara Kontinu - Wa Ode Yani; Ratna; Rahmanpiu (Sains: Jurnal Kimia dan Pendidikan Kimia, 2022)
Research has been carried out "Description of the Quality of Liquid Smoke from Pyrolysisof Coconut Shell with Continuous Air Flow Method". This study aims to describe the quality ofthe results of the separation of coconut shell liquid smoke by filtration and distillationmethods. The liquid smoke used is 600 mL which has a pH value of 2.99, acetic acid contentof 2.48% and a total phenol content of 3.16% which is filtered to produce a pH value of 2.98,acetic acid content of 2.5% with phenol content. a total of 4.03% then followed by distillationas much as 350 mL and obtained a distillate with a pH value of 2.96. The method used todetermine the acetic acid content of the liquid smoke distillate was the titration method andthe total phenol content was determined by the Folin-Ciocalteu method. Liquid smokedistillate has an acetic acid content of 2.51% with a total phenol content of 4.91%.